2015
DOI: 10.1089/brain.2014.0279
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Default Mode Network in High School Football Athletes Due to Repetitive Subconcussive Mild Traumatic Brain Injury: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Long-term neurological damage as a result of head trauma while playing sports is a major concern for football athletes today. Repetitive concussions have been linked to many neurological disorders. Recently, it has been reported that repetitive subconcussive events can be a significant source of accrued damage. Since football athletes can experience hundreds of subconcussive hits during a single season, it is of utmost importance to understand their effect on brain health in the short and long term. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 53 publications
13
145
0
Order By: Relevance
“…Recent studies suggest that subconcussive hits may relate to within-DMN connectivity, and so it is possible that this may have contributed to our findings. 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that subconcussive hits may relate to within-DMN connectivity, and so it is possible that this may have contributed to our findings. 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…Whether these changes result in long-term deficits likely depends on a variety of, as yet unknown, factors but it has been established that up to 72% of a typical high school football team exhibits changes that persist well into the off season when examined using functional MRI . In addition, resting state functional MRI imaging has demonstrated significant differences between collision sport athletes at their pre-season evaluation and non contact sport controls (Abbas et al, 2015a(Abbas et al, , 2015bBailes et al, 2013;Johnson et al, 2014;Johnson et al, 2012;McKee et al, 2009;Talavage et al, 2014). Taken together, these data indicate that elucidating which physical insults eventually lead to traumatic brain injury requires a characterization of the overall distribution of head impacts experienced by athletes during competition.…”
Section: Introductionmentioning
confidence: 90%
“…More importantly, studies looking at all levels of soccer play have shown that participation in soccer is associated with neurological deficits, even in the absence of a head injury diagnosis (Matser et al, 1999;O'Kane et al, 2014;Witol and Webbe, 2003). It has also been shown that subconcussive hits (defined as head impacts inducing no readily observable symptoms) in contact sports have the ability to cause neurophysiological changes that accumulate from one season to the next (Abbas et al, 2015a(Abbas et al, , 2015bBailes et al, 2013;Breedlove et al, 2014). Whether these changes result in long-term deficits likely depends on a variety of, as yet unknown, factors but it has been established that up to 72% of a typical high school football team exhibits changes that persist well into the off season when examined using functional MRI .…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, recent work has demonstrated that between 70% and 95% of high school football athletes exhibited substantial neurophysiological changes without easily identifiable symptoms. [4][5][6][7][8][9][10] These changes depend primarily on the number and rate of head impacts as well as their magnitude and location. The effects persist well into the offseason and may not resolve by the beginning of the subsequent season.…”
mentioning
confidence: 99%